Physical applications of homogeneous balls - Friedman Yaakov; Scarr Tzvi (Boston Birkhauser, 2005)
The first three chapters discuss the occurrence of bounded symmetric domains (BSDs) or homogeneous balls and their algebraic structure in physics. The book further provides a discussion of how to obtain a triple algebraic structure associated to an arbitr
Keywords: Homogeneous spaces; Mathematical physics-mathematical models; Special relativity(Physics)